PENANDA GENDER DALAM DRAMA YAMADA AND THE SEVEN WITCHES SUATU KAJIAN SOSIOLINGUISTIK - Novira Pratiwi; Mangatur Sinaga; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Japanese language has a variety of informal languages that are used by men and women as a characteristic of gender that consist of male (danseigo) and female (joseigo) languages. Male and female languages have their own gender markers for each element of the sentence. The use of various languages is widely available in media such as drama, songs, manga, magazines or television shows. This study aimed to explain the gender markers contained in one of Japanese dramas and the factors that cause these gender markers. This study used sources from a Japanese drama titled Yamada and the Seven Witches. This drama consists of eight episodes and and its genre is mistery and comedy. The technique used during data collection was the listening method, then analyzed by using Agih method. There is an advanced technique of the Agih method called the technique of reading markers to collect markers contained in the drama.Based on the data analysis, there were five markers of male and female languages found. The five markers were pronouns of person (ninshou dameishi), final particles (shujoushi), candoushi, nouns (meishi), and verbs (doushi). The five markers were then described using the model of speaking theory. According to the results, there were two factors that influenced the differences in gender markers in the drama of Yamada and The Seven Witches, namely the interlocutor and the situation. If the interlocutor were a respected person and or in a formal situation, then the speakers would used a variety of standard languages, but if on the contrary, then the speaker would use a variety of language respectively.Key Words: Gender Markers, Male Language Variety, Female Language Variety